Sixth grave on the edge - Jones, Darynda (Jones, Darynda. Charley Davidson, 2014)
Wanting to learn more about Reyes Farrow's past after accepting his proposal, grim reaper Charley Davidson investigates his childhood abduction at the same time she is threatened by a crime syndicate to hunt down a witness who is testifying against a mob boss.